2017
DOI: 10.1016/j.iac.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fungi in Atopic Dermatitis

Abstract: There is little doubt that Malassezia spp plays a role in atopic dermatitis because it may interact with the local skin immune responses and barrier function, and sensitization against this skin-colonizing yeast can correlate with disease activity. Also, antifungal therapy shows beneficial effects in some patients. However, the pathogenetic mechanism and mutual interaction between Malassezia spp and atopic dermatitis still remain partly unclear and need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 63 publications
(43 reference statements)
0
28
1
3
Order By: Relevance
“…Possible causes include a false positive IDT result in a dog with atopic‐like dermatitis and additional unrecognized FIAD or environmental hypersensitivities. It is also currently unknown if dogs could develop auto‐immunity to Malassezia allergen analogues as recognized in humans …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible causes include a false positive IDT result in a dog with atopic‐like dermatitis and additional unrecognized FIAD or environmental hypersensitivities. It is also currently unknown if dogs could develop auto‐immunity to Malassezia allergen analogues as recognized in humans …”
Section: Discussionmentioning
confidence: 99%
“…play multiple roles in the pathogenesis of human atopic dermatitis (AD). Malassezia dermatitis and immunoglobulin E (IgE)‐mediated hypersensitivity to Malassezia spp may cause exacerbation of clinical signs . Hypersensitivity to Malassezia pachydermatis also occurs in atopic dogs; hereafter designated as MHS .…”
Section: Introductionmentioning
confidence: 99%
“…According to the PubMed database, more than 300 research articles on the association between AD and Malassezia were published in between 1985 and 2018. This number included several extensive reviews, analysing multiple aspects of the issue including epidemiology, mycological, immune response and therapy. The number of papers covering Malassezia in the title and abstract exceeded 1760 (29.11.2018).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…According to the PubMed database, more than 300 research articles on the association between AD and Malassezia were published in between 1985 and 2018. This number included several extensive reviews, 1,[81][82][83]…”
Section: Ther Apeutic Implic Ationsmentioning
confidence: 99%
“…Recent studies have revealed that the fungi compose 1% to 22% of the normal skin microbiome, the most common species being Malassezia. 45 Malassezia spp rely on exogenous lipids for their metabolic requirement. Malassezia spp, as part of the normal skin microbiome, interact with cutaneous dendritic cells or lymphocytes.…”
Section: Allergic Dermatitismentioning
confidence: 99%